Changes in some biochemical parameters in small ruminant theileriosis - Gunes, N.; Arsoy, D.; Aktas, M.; Ozubek, S.; Ozuicli, M.; Aydin, L.; Selcuk, O. (National Centre for Agrarian Sciences, 2016)
The aim of this study was to determine changes in some biochemical parameters in the healthy and infected sheeps and goats with Theileriosis. Sixty-five sheep and 67 goats were used in the study. Blood samples were tested for the presence of Theileriosis using PCR and RLB. 3.07% of sheep and 3.06% of goats blood samples were found positive with Theileria ovis. We observed decreases in the levels of total protein, albumin, glucose and increases in ALT and AST values in the infected animals compared with the healthy group. This study suggests that changes in some biochemical parameters may occur and in terms of PCR can be detected in infected animals that are in the early stage of disease and do not show any clinical symptoms. © 2016, National Centre for Agrarian Sciences. All rights reserved.
Keywords: Biochemical parameter; PCR; Small ruminant; Theileriosis